2017
DOI: 10.1111/jch.13041
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and the diagnostic accuracy for primary aldosteronism

Abstract: The effects of body mass index (BMI) on the diagnostic accuracy of primary aldosteronism (PA) are inconsistent, and are important in light of the high prevalence and the frequent co-occurrence of obesity and hypertension. The current included 59 adult subjects that underwent a step-wise evaluation for PA, using aldosterone-to-renin ratio (ARR) for case detection, and plasma aldosterone concentration (PAC) after saline suppression test (sPAC) and/or 24hr urinary aldosterone after oral sodium loading for case co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…Goodfriend et al [ 9 ] reported a positive correlation between PAC and VFA in women with obesity without PA and in those with essential hypertension. Tirosh et al [ 26 ] reported a positive quadratic (U-shaped) correlation between PAC and BMI, not only in non-PA patients, but also in those with PA. Considering those reports, the relationship has remained unclear between PAC and BMI, waist circumference, and visceral fat in patients with PA.…”
Section: Discussionmentioning
confidence: 99%
“…Goodfriend et al [ 9 ] reported a positive correlation between PAC and VFA in women with obesity without PA and in those with essential hypertension. Tirosh et al [ 26 ] reported a positive quadratic (U-shaped) correlation between PAC and BMI, not only in non-PA patients, but also in those with PA. Considering those reports, the relationship has remained unclear between PAC and BMI, waist circumference, and visceral fat in patients with PA.…”
Section: Discussionmentioning
confidence: 99%
“…In a large cohort of newly diagnosed hypertensive patients, in whom treatment with a calcium channel blocker, an alpha-adrenoceptor blocker or their combination was permitted, Rossi et al 6 found that despite a positive association between BMI and plasma aldosterone levels, in particular in overweight and obese individuals, the ARR did not correlate with BMI. The latter was also true in a smaller, prospective study (n = 59) in patients suspected of having PA. 11 In that study, the ARR accuracy was higher in patients with BMI <30 compared with obese patients, when using values >20 as the ARR cutoff point. It should be noted that when antihypertensive treatment could not be safely withheld, patients could not only be treated with verapamil, doxazosin, and terazosin but also with hydralazine, a drug with a well-known stimulating effect on the renin-angiotensin-aldosterone system.…”
Section: Body Mass Indexmentioning
confidence: 76%
“…One study in PA patients reported a U-shaped correlation between PAC and BMI [ 26 ]. However, a study by Rossi et al found no significant correlation between BMI and PAC [ 23 ].…”
Section: Discussionmentioning
confidence: 99%